RSM: Reducing Mutation Testing Cost Using Random Selective Mutation Technique - Falah, Bouchaib; Akour, Mohammed; Bouriat, Salwa (Malaysian Journal of Computer Science, 2015)
Mutation testing has been neglected by researchers because of the high cost associated with the technique. To manage this issue, researchers have developed cost reduction strategies that aim to reduce the overall cost of mutation, while maintaining the effectiveness and the efficiency of testing. The purpose of this research paper is to present a new cost reduction strategy that cuts the cost of mutation testing through reducing the number of mutation operators used. The experimental part of the paper focuses on the implementation of this strategy on five different java applications. The results of the experiment areused to evaluate the efficiency and quantify the savings of our approach compared to two other existing mutation testing strategies.